Brain activation in response to visual sexual stimuli in male patients with right middle cerebral artery infarction: The first case-control functional magnetic resonance imaging study. Issue 21 (28th May 2021) - Park, Jae Hyeon; Kim, Eunkyung; Cho, Hyungpil; Park, Dong Woo; Choi, Joonho; Jang, Seong Ho
Abstract : Abstract: Sexual dysfunction is a common problem after cerebral infarction; however, little is known about sexual arousal in poststroke patients. Thus, this study aimed to investigate brain activation in response to visual sexual stimuli in patients with right middle cerebral artery (MCA) territory infarction using functional magnetic resonance imaging (fMRI). Using fMRI in 20 participants (11 right MCA infarction patients and 9 age-matched healthy controls), we assessed brain activation elicited by visual sexual stimuli (erotic images) and visual nonsexual stimuli (landscape images). In right MCA infarction patients, the left dorsolateral prefrontal cortex and the left frontal subgyral area were more strongly activated by visual sexual stimuli than by nonvisual sexual stimuli. Brain areas that were more activated by visual sexual stimuli in right MCA infarction patients than in controls included the right parahippocampal gyrus and the bilateral frontal subgyral area. These fMRI results suggest that brain activation patterns in response to visual sexual stimuli might be influenced by right MCA infarction. Further research is needed to explore the association between sexual dysfunction and brain activation in poststroke patients.